INTERNAL CHARGE REDISTRIBUTION AND CURRENTS IN CANCEROUS LESIONS (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
The tissues in biological objects from the point of view of electromagnetic effects have to be modeled by not only their conductivity. The electric field induced double ionic layer, constructed by electrolytic diffusion, has to be counted. We describe this phenomenon by micro (frequency dispersion phenomena), and by macro (interfacial polarization), as well as more generalized by Nernst-Planck cells. The results are applied to cancerous tissues in the healthy neighborhood. Our objective is to show the space charge distribution and redistribution that generate injury currents and other internal currents in the development of cancer. We show some aspects of the theoretical basis of modulated electro-hyperthermia (mEHT, trade name oncothermia, also used name: nanothermia), which uses an anti-injury current in the micro-range to limit the proliferation process, similar to the macro-range electrochemotherapy (ECT) processes.